Defusing the Director Liability Crisis: The Strategic Management of Legal Threats - Kaplan, Marilyn R.; Harrison, J. Richard (Organization Science, 1993)
Boards of directors have been substantially affected by recent changes in their legal environment. The most profound change has been in the area of director liability. New legislation and regulations and a series of court decisions increased the extent to which directors are held accountable for their actions and those of their organizations. These changes resulted in increased liability exposure for directors and a crisis in director liability insurance. Corporations have successfully developed strategies to manage the adverse consequences of these changes in the legal environment. This paper develops an extension of resource dependence theory to enable us to analyze events surrounding the director liability crisis from the perspective of the corporation. It then reviews the legal forces which have affected boards of directors. The concept of director liability is discussed, including the business judgment rule, which has historically protected the decision making discretion of boards. Indemnification and director liability insurance, which provide protection from monetary penalties against directors arising from liability suits, are also described. Recent environmental changes which have affected director protection from liability are then examined. These include legislation specifying certain director responsibilities and granting additional enforcement powers to federal regulatory agencies, court decisions which expanded the personal liability of directors in several important ways, and changes in director liability insurance policies and markets. These developments increased the liability exposure of corporate directors and precipitated the director liability crisis of 1986. Corporations responded to this threat by making changes in board composition, director compensation, and board decision making structures and processes; by developing alternative forms of director liability insurance; and by lobbying for legislation providing greater liability protection for directors. These actions are interpreted within the framework of resource dependence theory. Implications for future research are also discussed.